2008
DOI: 10.1111/j.1469-8137.2008.02411.x
|View full text |Cite
|
Sign up to set email alerts
|

Methoxyl groups of plant pectin as a precursor of atmospheric methane: evidence from deuterium labelling studies

Abstract: Summary• The observation that plants produce methane (CH 4 ) under aerobic conditions has caused considerable controversy among the scientific community and the general public. It led to much discussion and debate not only about its contribution to the global CH 4 budget but also about the authenticity of the observation itself. Previous results suggested that methoxyl groups of the abundant plant structural component pectin might play a key role in the in situ formation process of CH 4 . Here, this effect is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
137
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(155 citation statements)
references
References 20 publications
9
137
3
Order By: Relevance
“…However, the potential role of plants has become now further controversial after a recent study by Dueck et al (2007) questioning the measurements of Keppler et al (2006). Using an independent method based on 13 C labelling and laser-based measurements, Dueck et al (2007) did not find evidence for substantial CH 4 emissions of plants under aerobic conditions while Keppler et al (2008) confirm their earlier work by providing evidence that methoxyl groups of pectin can act as a source of atmospheric CH 4 under aerobic conditions. Nevertheless, the contribution of emissions from plants to the global methane budget remains uncertain.…”
Section: Discussion Of the Multi-year Xch 4 Data Setsupporting
confidence: 74%
“…However, the potential role of plants has become now further controversial after a recent study by Dueck et al (2007) questioning the measurements of Keppler et al (2006). Using an independent method based on 13 C labelling and laser-based measurements, Dueck et al (2007) did not find evidence for substantial CH 4 emissions of plants under aerobic conditions while Keppler et al (2008) confirm their earlier work by providing evidence that methoxyl groups of pectin can act as a source of atmospheric CH 4 under aerobic conditions. Nevertheless, the contribution of emissions from plants to the global methane budget remains uncertain.…”
Section: Discussion Of the Multi-year Xch 4 Data Setsupporting
confidence: 74%
“…soil or plant water) and whether plants have their own mechanism(s) to produce CH 4 have been debated (Bruhn et al, 2012;Keppler et al, 2009;Nisbet et al, 2009). Evidence is now accumulating to indicate that plants can produce CH 4 even in the presence of oxygen (Bruggemann et al, 2009;Bruhn et al, 2009Bruhn et al, , 2014Cao et al, 2008;Fraser et al, 2015;Keppler et al, 2008;Lenhart et al, 2014;McLeod et al, 2008;Messenger et al, 2009;Mikkelsen et al, 2011;Reid, 2009, 2011;Sanhueza and Donoso, 2006;Sinha et al, 2007;Vigano et al, 2009Vigano et al, , 2008Wang et al, 2009aWang et al, , 2009bWang et al, , 2011aWatanabe et al, 2012;Wishkerman et al, 2011).…”
Section: Plantsmentioning
confidence: 99%
“…pectin, lignin, cellulose and leaf surface wax) (Bruhn et al, 2014;Keppler et al, 2008;McLeod et al, 2008;Messenger et al, 2009;Vigano et al, 2009Vigano et al, , 2008 have been extensively tested. The majority of studies reported substantial CH 4 emissions, while Bowling et al (2009) reported no evidence for substantial CH 4 emissions by a conifer forest under high UV radiation, to which a soil CH 4 sink might contribute.…”
Section: Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that CH 4 can be produced abiotically from plant material by exposing it to ultraviolet (UV) irradiation [15][16][17][18] . A reaction of reactive oxygen species (ROS) with methoxyl groups of pectic polysaccharides was suggested as a possible route to CH 4 formation under UV radiation 19 .…”
mentioning
confidence: 99%